Effects of dietary l-tryptophan on the agonistic behavior, growth, and survival of freshwater crayfish Astacus leptodactylus Eschscholtz - Harlioglu, Muzaffer Mustafa; Harlioglu, Ayse Gul; Yonar, Serpil Mise; Duran, Tuba Cakmak (Springer, 2014)
In this study, the effects of dietary tryptophan (a precursor of 5-hydroxytryptamine, 5-HT, serotonin) on the agonistic behavior, growth, and survival of freshwater crayfish were investigated. For this aim, a control diet (D1) and three experimental diets (D2, D3, and D4) were prepared. D1 contained no additional tryptophan (TRP), but D2, D3, and D4 diets were supplemented with TRP at 0.50, 0.75, and 1.00 % in dry diet, respectively. The control contained 0.33 % TRP. Results revealed that higher supplemental dietary TRP levels caused a significant decrease in the aggressive behavior (P < 0.05), but an increase in the calmness of crayfish. In addition, the results showed that 5-HT levels in the hemolymph before the fight (after 15 days of feeding; resting) were significantly different (P < 0.05) between D1 and D4. There was a significant difference (P < 0.05) in the 5-HT level of hemolymph between the crayfish fed control and D4 after 15 days of feeding. However, after the fight, 5-HT concentration was significantly higher (P < 0.05) in TRP-supplemented A. leptodactylus as compared with the control. The findings of this study showed that supplemental dietary TRP caused a significant increase (P < 0.05) in the growth and survival rate of A. leptodactylus. The crayfish fed D4 had the best survival rate at the end of the experiment (91.60 % in August). The findings of this study also showed that difference in survival rate between the crayfish fed control and D2 in June, July, and August was not significant (P > 0.05). In addition to these, supplemental dietary TRP gave rise to significantly higher specific growth rate (SGR) values in June and July (P < 0.05). For example, in June, it was 0.38 for the crayfish fed D4, 0.28 for the crayfish fed D3, 0.18 for the crayfish fed D2, and 0.13 for the crayfish fed control. However, in August, the highest SGR (0.56) was obtained from the crayfish fed control. The results also showed that the SGRs of females were lower than the males in June, July, and August (P < 0.05). In conclusion, this research shows that the aggressive behavior of A. leptodactylus can be suppressed, and rearing efficiency (i.e., increased growth and high survival rate) of this species can be improved by increasing TRP levels to 1.00 % in its diet.
Keywords: Crayfish; Tryptophan; Diet; Agonistic behavior; Survival; Growth